ANALISIS PENERAPAN SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN TERPADU (SIMPEDU) PADA BADAN KEPEGAWAIAN DAERAH PROVINSI LAMPUNG - Agus Purnomo (e-JKPP, 2018)
ABSTRACTThe type of research used in this research is through qualitative research method approach. Qualitative data analysis process is done by data reduction phase, presentation of data (display) and draw conclusion (verification). Based on the result of the research, it can be concluded that the implementation of Integrated Personnel Management Information System at the Regional Personnel Board of Lampung Province has been run in accordance with the flow that must be undertaken, among others, include input sub-system, process sub-system and output sub-system. Obstacles encountered in the application of Integrated Personnel Management Information System at the Regional Personnel Board of Lampung Province, among others, infrastructure and human resources are inadequate, and local government support is still not optimal. Efforts that have been made in overcoming the obstacles of the implementation of Integrated Personnel Management Information System at the Regional Personnel Board of Lampung Province that is the human resources in the Field Documentation and Information Officer BKD Lampung Province should be included Training / training on SIMPEDU so that existing human resources can more controlled about SIMPEDU. Efforts that have not been done in overcoming the obstacles of the implementation of Integrated Personnel Management Information System at the Regional Personnel Board of Lampung Province is to integrate the application SIMPEDU to all OPD in the local government of Lampung Province.Keywords: Implementation, Integrated Personnel Management Information System